Links between migration and discrimination. European Network of Legal Experts in the non-discrimination field - De Schutter, Olivier (Luxembourg, 2009)
"This report aims at describing the links between nationality and the protection from discrimination under EU and international law, as well as in the domestic legal orders of the EU Member States. Its purpose is to identify whether third-country nationals are protected once they enter the European Union from discrimination on grounds of nationality, or from discrimination on grounds of race, ethnic origin or religion, in situations where nationality is used as a proxy for these grounds."